Sexual Function and Depressive Symptoms among Male North American Medical Students - Smith, James F. (2010)
INTRODUCTION: The role of sexuality as an association of medical student well-being has not been extensively studied. AIM: We explored the relationship between depressive symptoms, sexuality, and sexual dysfunction in male North American medical students. MAIN OUTCOME MEASURE: North American medical students were invited to participate in an Internet-based survey. The Center for Epidemiological Studies Depression Scale (CES-D) was utilized to screen for depressive symptoms. METHODS: Subjects completed an ethnodemographic survey, a sexuality survey, and instruments for the quantification of anxiety, sexuality, and psychosocial function. Descriptive statistics, odds ratios (ORs), and logistic regression were used to analyze our data. RESULTS: There were 844 male subjects with complete data on the CES-D and the Spielberger State-Trait Anxiety Index. Depressive symptoms (CES-D ≥ 16) were present in 37% of respondents and were more common in subjects with greater levels of anxiety. Subjects who were in sexual relationships and/or had frequent sexual activity were less likely to be depressed compared to other subjects. Erectile dysfunction (ED) was associated with significantly greater likelihood of depressive symptoms (OR 2.90 and 9.27 for depressive symptoms in men with mild or moderate/severe ED relative to men without ED, P < 0.01). After adjusting for ethnodemographic and sexual history factors, ED remained significantly positively associated with depressive symptoms (OR 2.87 and 6.59 for depressive symptoms in men with mild or moderate/severe ED relative to men without ED after adjustment, P ≤ 0.01). Inclusion of data related to psychosocial/relationship factors in the multivariate model eliminated the significant association between ED and depressive symptoms (OR 1.59 and 2.29 for depressive symptoms in men with mild or moderate/severe ED relative to men without ED after adjustment with the Self-Esteem and Relationship quality instrument, P > 0.05), suggesting that psychosocial factors were more strongly associated with depressive symptoms than erectile function. CONCLUSION: Healthy sexuality and relationships may be protective against depressive symptoms in medical students. Attention to these factors may enhance medical student well-being. Smith JF, Breyer BN, Eisenberg ML, Sharlip ID, and Shindel AW. Sexual function and depressive symptoms among male North American medical students. J Sex Med 2010;7:3909–3917.